Evaluation of Cost Factors Influencing the Adoption of Sustainable Construction Practices in Abuja, Nigeria - Amina UTHMAN; Shamsuddeen SULAIMAN (FUDMA Journal of Engineering and Technology, 2025)
The adoption of sustainable construction practices is crucial in addressing environmental, economic and social concerns in the built environment. However, cost-related factors remain a significant barrier to their widespread implementation, particularly in developing countries like Nigeria. This paper, therefore, seeks to assess the cost factors influencing the adoption of sustainable construction practices in Abuja, Nigeria, with a view to improve cost efficiency. A quantitative research approach was adopted using self-administered questionnaires to collect data from experienced construction professionals registered with the Green Building Council of Nigeria (GBCN). A mixture of purposive and snowball sampling techniques was employed to select professionals with requisite experience and involvement in sustainable construction practice. Data collection was done using a questionnaire survey via self-administered questionnaires to experienced professionals. Data was analyzed using descriptive statistics, which is the relative importance index (RII), to rank the significance of various cost factors. The study revealed that the most significant cost factors include high initial capital costs, the expensive nature of sustainable materials, and limited financial incentives. Other critical cost factors identified include the cost of renewable energy systems, maintenance and operational expenses, poor knowledge of life-cycle costing, project financing challenges, and regulatory compliance costs. Despite these challenges, the study underscores the long-term economic benefits of sustainability through reduced operational costs and increased property value. To promote sustainable construction, the study recommends the development of financial support frameworks, such as grants and low-interest loans, increased availability of local sustainable materials and enhanced education on life-cycle costing to improve awareness through education and training. Addressing these cost factors is essential for fostering a more sustainable and cost-effective construction industry in Abuja, Nigeria.
Keywords: Cost factors, Financial incentives, Initial capital cost, Sustainable construction, Life-cycle cost.